Knowledge as an Asset and Knowledge Management - Sevinç Gülseçen (Türk Kütüphaneciliği)
The most valuable resource available to any organization today is its knowledge asset which is stored in processes and information systems, corporate data warehouses, employees’ brains, copyrights and patents. Knowledge management is the process of capturing, distributing, and effectively using this knowledge. The factors affecting Knowledge Management can be listed as follows: organizational culture, knowledge manager, the evolution of knowledge, knowledge polution and technology.